Impedance Spectroscopy of a Vibrating Wire for Viscosity Measurements - Janeiro, Fernando M. (2010)
Many routine viscosity measurement systems suffer from low accuracy and some are also operator dependant which creates repeatability problems. This paper describes the ongoing developments of a viscosity measurement system based on a vibrating wire cell. The proposed improvements include the simultaneous fitting of the magnitude and phase of the measured impedance and the test of different equivalent impedance circuits. Since the fitting function has a high number of search variables and contains many local minima, a hybrid method involving genetic algorithms as well as a traditional search algorithm is used. The system is tested with liquid diisodecyl phthalate (DIDP) and the viscosity results are compared to reference values available in the literature. A new equivalent impedance circuit is also suggested as one of the possible circuits to model the cell behavior in the future, when used with ionic liquids.